Methodological aspects of the anthropometric assessment in the Brazilian National Survey on Child Nutrition (ENANI-2019): a population-based household survey - Luiz Antonio dos Anjos; Haroldo da Silva Ferreira; Nadya Helena Alves-Santos; Maiara Brusco de Freitas; Cristiano Siqueira Boccolini; Elisa Maria de Aquino Lacerda; Inês Rugani Ribeiro de Castro; Virginia Gaissionok Mariz; Bruno Mendes Tavares; Denise Pretucci Gigante; Gilberto Kac (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: The article presents methodological aspects of anthropometric assessment of nutritional status in children under five years of age and their biological mothers. It discusses the strategies used for training and data collection in the Brazilian National Survey on Child Nutrition (ENANI-2019). ENANI-2019 is a population-based household survey conducted in 123 municipalities in Brazil's 26 states and the Federal District. The anthropometric measurements were body mass and length/stature. The equipment was purchased according to its measurement capacity and precision, portability, and cost-benefit ratio after an extensive market search. The study used internationally established procedures described in manuals, videos, and support material developed for the study by a group of experts. The interviewers were trained to perform the anthropometric measurements and were assessed according to technical measurement error, which was considered adequate (0.30cm) for the children's length/stature measurements. Measurement errors were identified, and the interviewers were retrained when necessary. Of the 14,558 children in the sample, body mass and length/stature measurements were taken in duplicate in 13,835 and 13,693 children, respectively. The standardized methodological aspects will be helpful in future population studies and were essential for obtaining greater reliability in the data for generating current evidence on the anthropometric assessment of the nutritional status of Brazilian children under five years of age, allowing new perspectives for public policy development.